Time Dependent Scanning Path Optimization for the Powder Bed Fusion Additive Manufacturing Process. (January 2022) - Boissier, M.; Allaire, G.; Tournier, C.
Abstract: In this paper, scanning paths optimization for the powder bed fusion additive manufacturing process is investigated. The path design is a key factor of the manufacturing time and for the control of residual stresses arising during the building, since it directly impacts the temperature distribution. In the literature, the scanning paths proposed are mainly based on existing patterns, the relevance of which is not related to the part to build. In this work, we propose an optimization algorithm to determine the scanning path without a priori restrictions. Taking into account the time dependence of the source, the manufacturing time is minimized under two constraints: melting the required structure and avoiding any over-heating causing thermally induced residual stresses. The results illustrate how crucial the part's shape and topology is in the path quality and point out promising leads to define path and part design constraints. Highlights: First systematic use of geometric sensitivity approach for path optimization. Optimization under realistic partial differential equation constraint. Numerical tests for real materials with calibrated physical parameters.